2019
DOI: 10.1111/asj.13175
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fluid, feces, milk, water, feed, airborne dust, and bedding microbiota in dairy farms managed by automatic milking systems

Abstract: Microbiota of the gut, milk, and cowshed environment were examined at two dairy farms managed by automatic milking systems (AMS). Feed, rumen fluid, feces, milk, bedding, water, and airborne dust were collected and the microbiota on each was assessed by Illumina MiSeq sequencing. The most abundant taxa in feed, rumen fluid, feces, bedding, and water were Lactobacillaceae, Prevotellaceae, Ruminococcaceae, Ruminococcaceae, and Lactobacillaceae, respectively, at both farms. Aerococcaceae was the most abundant tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…belong to, was expected to be high. However, the abundance of Moraxellaceae recorded in this study (0.24%–12.9%) appeared to be the same as those reported for Holstein milk (Nguyen et al., 2019; Wu et al., 2019). Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…belong to, was expected to be high. However, the abundance of Moraxellaceae recorded in this study (0.24%–12.9%) appeared to be the same as those reported for Holstein milk (Nguyen et al., 2019; Wu et al., 2019). Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 89%
“…It is difficult to assert that the microbiota data of this study was representative of Jersey cow milk, because milk microbiota can be altered by environmental factors including farm management and season. However, the finding that the relative abundance of Pseudomonadaceae was high compared to that reported for Holstein milk (Nguyen et al., 2019; Wu et al., 2019) was noteworthy. Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…3a) [23]. Previous studies which sampled microbes from a cowshed environment, found similar bacterial communities, including Ruminococcaceae members which were also distinctly enriched in fly samples from farms compared to hospitals and homes in this study [24, 25] (Fig. 3).…”
Section: Discussionsupporting
confidence: 74%
“…The association of Dothideomycetes, including Pleosporales, and Tremellomycetes with milk from organic farms is surprising and unknown, since fungi belonging to these classes often include plant pathogens that grow on wood debris or decaying leaves, yet their presence have been reported in the environment of dairy farms (Mbareche et al, 2018) and in shelves used for ripening of cheese (Guzzon et al, 2017). Airborne dust microbiota and housing conditions, such as bedding, have been described to affect milk microbiota composition, because the teats of cows contact directly with the bedding material when the cows are resting (Nguyen et al, 2019;Wu et al, 2019) and the teat microbiota is a known source of contamination of the milk microbiota (Verdier-Metz et al, 2009;Doyle et al, 2017). Perhaps the reported fungi in this study occur more commonly within the environment of organic farms in particular substrates, but further research is needed to identify the source of these fungi and to evaluate their importance in the context of dairy farms.…”
Section: Residualmentioning
confidence: 99%